1981
DOI: 10.1364/josa.71.000723
|View full text |Cite
|
Sign up to set email alerts
|

Color and conspicuousness

Abstract: The principle that things are easier to find if they contrast with their environment is expressed quantitatively. Two indices of conspicuousness, relative fixation rate and search time, are shown to be related to the color difference between the target and background objects. The color difference equations used are CIELAB, CIELUV, and the Judd modification of the index of fading. None of the equations is superior to the others. Furthermore, neither Judd's modification nor Semmelroth's adjustment accounts for e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
51
0

Year Published

1985
1985
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 99 publications
(53 citation statements)
references
References 19 publications
2
51
0
Order By: Relevance
“…However, most researchers have abandoned it (e.g. Wolfe, 1998a), as evidence accumulated to suggest that conjunction search can sometimes be quite efficient (Nakayama & Silverman, 1986) and that (as mentioned above), feature search can be inefficient when targets and distractors are very similar (Carter, 1982;Carter & Carter, 1981;Nagy & Sanchez, 1990). In addition, as is well known, sizable display set size slopes might be predicted by either a serial search or a limited-capacity parallel search in which processing is always parallel, but worsens when display set size increases (Townsend, 1976(Townsend, , 1990Wolfe, 1998a).…”
Section: Attentional Capacity Limits and The Serial/parallel Dichotomymentioning
confidence: 99%
See 1 more Smart Citation
“…However, most researchers have abandoned it (e.g. Wolfe, 1998a), as evidence accumulated to suggest that conjunction search can sometimes be quite efficient (Nakayama & Silverman, 1986) and that (as mentioned above), feature search can be inefficient when targets and distractors are very similar (Carter, 1982;Carter & Carter, 1981;Nagy & Sanchez, 1990). In addition, as is well known, sizable display set size slopes might be predicted by either a serial search or a limited-capacity parallel search in which processing is always parallel, but worsens when display set size increases (Townsend, 1976(Townsend, , 1990Wolfe, 1998a).…”
Section: Attentional Capacity Limits and The Serial/parallel Dichotomymentioning
confidence: 99%
“…This "pop-out" effect is generally agreed to reflect spatially parallel processing (Treisman & Gelade, 1980). When the target/distractor difference is very subtle, however, even this sort of singleton search often shows a substantial display-set-size effect (Carter, 1982;Carter & Carter, 1981;Nagy & Sanchez, 1990). Thus, a person wearing red cannot be so readily picked out from a crowd of people all wearing a slightly pinkish red chartreuse.…”
Section: Introductionmentioning
confidence: 99%
“…E. C. Carter and R. C. Carter (1981) showed that the color difference between a target and distractors determined the conspicuousness of the target, as measured by relative fixation rate and reaction time. Following the same line, R. C. Carter (1982) found that the slope of the search time function increased as the target and distractors became more similar in color.…”
mentioning
confidence: 99%
“…These findinas are Particularly interestinq in light of the results of Carter & Carter (1981) and Jacobsen (in press).…”
Section: J)mentioning
confidence: 77%
“…This estimate of color difference has also * been shown to be a qood predictor of visual search performance (Carter & Carter, 1981).…”
Section: Introductionmentioning
confidence: 98%